2012
DOI: 10.2341/11-030-l
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Effect of Delaying Toothbrushing With Toothpaste on Enamel Microhardness Subsequent to Bleaching the Teeth With 15% Carbamide Peroxide

Abstract: Delaying oral hygiene procedures during bleaching does not seem to cause any change in enamel microhardness. SUMMARYChanges in enamel surface microhardness as a result of bleaching with carbamide peroxide in various in vitro conditions have been reported. The present study evaluated the effect of oral hygiene procedures on enamel microhardness at three time intervals following bleaching with 15% carbamide peroxide. Although this was an in vitro study, the purpose was to address whether or not a patient's tooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…As demineralization was not detected in this study, the increase in roughness that the enamel underwent, which was stated by Cakir et al (2011) [ 1 ]; Izquierdo-Barba et al (2015) [ 8 ]; Souza et al (2010) [ 13 ]; Pedreira de Freitas et al (2010) [ 24 ]; Zimmerman et al (2010) [ 25 ]; Gjorgievska and Nicholson (2011) [ 26 ]; Navimipour et al (2012) [ 27 ]; Navimipour et al (2013) [ 28 ]; and Sa et al (2013) [ 29 ], is probably due to the property of hydrogen peroxide that denatures proteins which are present in the region of interprismatic enamel, creating valleys, as described by Pedreira de Freitas et al (2010) [ 24 ] and Zimmerman et al (2010) [ 25 ].…”
Section: Discussionsupporting
confidence: 65%
“…As demineralization was not detected in this study, the increase in roughness that the enamel underwent, which was stated by Cakir et al (2011) [ 1 ]; Izquierdo-Barba et al (2015) [ 8 ]; Souza et al (2010) [ 13 ]; Pedreira de Freitas et al (2010) [ 24 ]; Zimmerman et al (2010) [ 25 ]; Gjorgievska and Nicholson (2011) [ 26 ]; Navimipour et al (2012) [ 27 ]; Navimipour et al (2013) [ 28 ]; and Sa et al (2013) [ 29 ], is probably due to the property of hydrogen peroxide that denatures proteins which are present in the region of interprismatic enamel, creating valleys, as described by Pedreira de Freitas et al (2010) [ 24 ] and Zimmerman et al (2010) [ 25 ].…”
Section: Discussionsupporting
confidence: 65%
“…However, in our previous study, which measured enamel microhardness in the same experimental conditions, it was shown that toothbrushing immediately after bleaching has no detrimental effect on enamel microhardness. 34 Another study has demonstrated that toothbrushing with abrasive toothpastes with or without fluoride after bleaching with 10% carbamide peroxide increases enamel surface roughness. 2 Therefore, in the present study a low-abrasive fluoridated toothpaste recommended by the bleaching agent manufacturer was used for toothbrushing in all the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our SEM results, it can be observed, with the exception of the group that only used brushing with toothpaste and whitening pen, that all the groups in the study suffered modifications in the enamel's surface (accepting therefore the hypothesis of our second variable); interestingly these same groups suffered significant decrease in the Vickers hardness, showing loss in the mineral of the enamel as well as visible changes in the morphology of the surface. A possible explanation for this phenomenon is that the whitening process is produced by the oxidation of the pigments that are found in the dental enamel by the chemical products that are found in the whitening agents (22). In our search for literature, no articles were found that evaluate the effects that the oral hygiene auxiliaries and the whitening effects have on the micro-hardness and surface of the dental enamel.…”
Section: Discussionmentioning
confidence: 99%